دور البنوك التجارية في تحقيق التنمية المحلية -دراسة ميدانية لبنك التنمية المحلية لولاية المسيلة- - دامة مروان (جامعة محمد بوضياف المسيلة, 2018)
تناولت هده الدراسة المكانة والأهميةالإستراتجيةالذي تلعبه البنوك التجارية في تمويل النشطة الاقتصادية لإحداث تنمية محلية وخلق ثروة وطنية ودلك من خلال مساهمتها في توفير مناصب شغل وزيادة الناتج المحلي وخلق قيمة مضافة والمساهمة في التنمية الاجتماعية ومحاربة ظاهرتي البطالة والفقر ’ لكن رغم رغم دلك مازالت تواجه العديد من الصعوبات والمشاكل التي تحد من قدراتها حيث يعتبر مشكل التمويل – الإقراض- أهم الصعوبات التي تواجه المستثمرين ودلك بسبب المخاطر التي تحملها هده الأخيرة خاصة في بداية النشاط والاكتر من دلك هو السياسة المتبعة من قبل البنوك في عملية منح القروض – البيروقراطية – والروتين الإداري و\دلك من خلال الإجراءات والشروط المعقدة في دراسة الملفات والضمانات التي يتوجب على المستثمرين توفيرها بالنوعية والقيمة المناسبة على هدا المنوال سيحد من الدور الذي يلعبه البنك التجاري في تحقيق تنمية محلية وهدا ما لمسناه في الدراسة الميدانية في بنك التنمية المحلية – وكالة المسيلة – لدلك يجب على الجهات الوصية الاهتمام وأخد هدا الملف بعين الاعتبار ومحاولة تسهيل العلاقة والعملية بين البنوك التجارية والمستثمرين ودلك من خلال العمل على خلق تسهيلات التي بدورها تعمل على خلق ثروة وطنية وتنمية محلية وبعد استراتيجي للنهوض بالاقتصاد الوطني This study dealt with the position and importance of commercial banks in financing economic activity to create local development and a national wealth through its contribution to the provision of posts, increasing domestic output, creating value added, contributing to the social development and fighting theunemployment phenomena and poverty. But despite of these difficulties and problems that limit their capabilities where the problem of financing - loaning - the most important difficulty that faces investors, because of the risks by this latter, especially at the beginning of the activity and more of it, is the banks' policies in work. The granting of loans - the bureaucracy - and the administrative routine through the complex procedures and conditions in the study of the files and guarantees that investors must provide with the appropriate quality and value in this manner will limit the role played by the Commercial Bank in achieving local development and this is what we saw in the field study in the BanqueDevelopement Local BDL - M'sila Agency - For this purpose, the authorities should take this issue in consideration and try to facilitate the relationship and the procedures between the commercial banks and the investors, and work through creating facilities that in turn create national wealth and local development and dimensional strategy to the advancement of the national economy.
Keywords: البنوك التجارية، التنمية المحلية، بنك التنمية المحلية